Performance of cermet tools : applying negative rake angles high speed machining - Adesta, Erry Yulian Triblas; Muhammad, Riza (LAP Lambert Academic Publish GmbH & Co, 2010)
Many research and development works have been carried out in the area of high speed turning. Cermet tools have been employed for high speed machining for a long time due to their high wear resistance and high hot hardness. In the current work, research is focused on the analysis of wear behavior of cermets applying negative rake angles during high speed machining. In addition to that, cutting temperature is also integrated in this research due to its significant roles in high speed machining. Those facts and evidences have formed the rationale of this research. Hence, the aim of this research is to investigate performance of cermet tools applying negative rake angles during high speed machining.